Condições de vida e saúde de pessoas vivendo com HIV/Aids na Paraíba: segurança alimentar, qualidade de vida e estado nutricional - Lima, Rafaela Lira Formiga Cavalcanti de (2016)
A significant number of people are living with human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (Aids) in the world, currently. With the increased survival rate provided by antiretroviral therapy, HIV-infected people now have concerns about their quality of life (QOL). Food insecurity corroborates with the socio-economic impacts arising from the disease while the HIV infection tends to aggravate the situation of food insecurity by the fact that it reduces work capacity and productivity of affected individuals. Nutrition intervention studies have demonstrated that the nutritional assistance promotes good responses to treatment and improves quality of life of people with HIV. In this context, the present thesis has as main objective to meet the conditions of life and health of people living with HIV and Aids (PLWHA) in the light of the situation of food insecurity, quality of life and nutritional status. This is a cross-sectional analytic study, involving 481 PLWHA answered in a reference service of the State of Paraiba-Brazil, held between the months of September and December 2015. Food insecurity was assessed using the Brazilian range of food insecurity and the quality of life was measured using the WHOQOL-Bref HIV. The association between food insecurity and socio-demographic, economic and health characteristics was evaluated by the Chi-square test. To assess quality of life scores in relation to the characteristics mentioned, we used nonparametric tests: Kruskal Wallis and Mann Whitney. In order to evaluate the associations between quality of life and food insecurity, the variables that showed significant differences to the quality of life were included in the multiple regression model of Poisson. A decision tree model was generated for the purpose of classifying the self-evaluation of the quality of life. The results show that in addition to the fragility that resulted from infection with HIV, people living with HIV/Aids demonstrate other types of vulnerability: average age above 30 years, significant number of women, low economic condition, low education level, high number of people employed or receiving pensions and aid. The prevalence of food insecurity found was considered high, 62.8%. The average scores of all domains of quality of life, were considered good. The lowest average scores were found in the environmental domain, followed by the domain level of independence and the largest in the field, in the physical domain of spirituality and psychology. Lower average scores in the areas were observed among women, individuals with lower per capita income, low education, without occupation and inactive. Food insecurity increases the prevalence of a worse quality of life in the areas: physical (19%), level of independence (20%), environment (23%) and on assessment of QOL (20%). PLWHA in food insecurity, regardless of the seriousness of the same average scores that are lower than those on food safety in all areas of quality of life, there was a significant difference (p < 0.01). Correlation exists between all domains of quality of life and food insecurity. The decision tree model generated contributes to the association between food insecurity and the quality of life. On the subjectivity and multidimensionality of quality of life, the findings of this study are relevant, contribute to filling existing gaps in the literature on the subject and need to be considered in order to promote a positive cycle of combat against HIV/Aids.